DEVELOPING A PREDECTION MODEL ABOUT THE DELINQUANCY OF COMPANIES USING THE NON FINANCIAL INDICATORS - Almoumany, Salam (European Scientific Journal, ESJ, 2013)
The main objective of the research is developing a mathematical model to predict the financial delinquency using non-financial indicators. The study sample consisted of (24) joint-stock industrial companies in Jordan (12 delinquent and 12 are not). The researcher considered the companies that experienced losses for two consecutive years or had been under liquidation action, as per the financial statements published in the Amman Stock Market during the period from 2000 to 2008 are delinquent, provided that they were established before the year 2000. To realize the objectives of this study in identifying the indicators of the financial delinquency of the sample companies, the research employed the multi discriminate analysis for defining the discriminate variables (discriminate equation), to develop the targeted model of the current study.